Host diet and evolutionary history explain different aspects of gut microbiome diversity among vertebrate clades - Nicholas D. Youngblut (Nature Portfolio, 2019)
Host phylogeny and diet are major explanatory factors of animal gut microbiome diversity, but our understanding of these associations is limited by a focus on captive animals and a narrow taxonomic scope. Here, the authors isolate evolutionary and ecological drivers of gut microbiomes from wild mammals, birds, reptiles, amphibians, and fish.